Advanced Sexual Counseling and How to Ask Patients About “Intimate Disclosure” - Marchand GJ; Meassick KS (Dove Medical Press, 2020)
Greg J Marchand, Katerina S Meassick Marchand Institute for Minimally Invasive Surgery, Mesa, AZ, USACorrespondence: Greg J MarchandMarchand Institute for Minimally Invasive Surgery, 10238 E. Hampton Ave., Suit 212, Mesa, AZ 85209, USATel +1-480-999-0905Email gm@marchandinstitute.orgAbstract: At the forefront of female sexual and reproductive health, OBGYNs play a pivotal role in assessing and managing sexual satisfaction and dysfunction. Satisfying sexuality often relates to a woman’s ability or likelihood to relay to her partner the steps and actions required for her to reach orgasm. Female orgasms, in contrast to male orgasms, can be related to different areas of stimulation and processes (clitoral/vaginal (G-spot)/anal). Despite this knowledge, OBGYNs rarely discuss orgasm with patients or the importance and vulnerability of disclosing this information to their partners to enhance sexual satisfaction. Many women may not realize that sexual complaints are an acceptable subject to discuss at gynecologic visits, while others may feel uncomfortable in general talking about sex. But as the topic of female sexual dissatisfaction becomes less taboo thanks to social media, patients are increasingly likely to turn to their health-care providers to evaluate and treat sexual complaints. While conducting a thorough history, sexual history, physical exam and laboratory tests can help to rule out any biological, physiological or psychological causes of sexual dissatisfaction, it is only one half of the equation. Discussion of the steps and actions required for them to reach orgasm with their partners is paramount in working to achieve satisfying sexuality and orgasm. Despite the importance of satisfying sexuality in a relationship, this topic often leads to feelings of trepidation and vulnerability on behalf of the patient. Recognizing and providing acknowledgment of these feelings help patients feel listened to and validated.Keywords: counseling, female orgasm, sexual counseling, sexual health, communication, satisfying sexuality